2013
DOI: 10.5539/enrr.v3n2p111
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality Assessment in the Vicinity of Quarry Site

Abstract: This study investigated air pollutants associated with quarry activities and the variation of the pollutants with distance from the drilling section. Air pollutants were monitored with the use of automatic air samplers with the exception of ozone (O 3 ) which was determined by iodometric method. All sampling were replicated three times. The data obtained were subjected to descriptive statistics, analysis of variance and correlation. Means were separated using Duncan Multiple Range test. Carbon monoxide and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 6 publications
5
29
0
Order By: Relevance
“…They observed significant dust retention within few tens of meters, which was perceived also in this study. Bada et al ( 2013 ) reports mass concentration in the same order of magnitude for TSP and PM as measured in this study. Degan et al ( 2013 ), Junttila et al ( 1996 ) and Olusegun et al ( 2009 ) measured approximately ten or more times higher and Golbabaei et al ( 2004 ) approximately 100-200 times higher concentrations compared to this study.…”
Section: Dust Mass Concentration Levelsmentioning
confidence: 58%
See 3 more Smart Citations
“…They observed significant dust retention within few tens of meters, which was perceived also in this study. Bada et al ( 2013 ) reports mass concentration in the same order of magnitude for TSP and PM as measured in this study. Degan et al ( 2013 ), Junttila et al ( 1996 ) and Olusegun et al ( 2009 ) measured approximately ten or more times higher and Golbabaei et al ( 2004 ) approximately 100-200 times higher concentrations compared to this study.…”
Section: Dust Mass Concentration Levelsmentioning
confidence: 58%
“…TSP concentrations were few hundreds of micrograms per cubic meter and PM concentrations were few tens of micrograms per cubic meter in both studies. PM concentrations had more variation being approximately 70 µg/m in study reported by Bada et al ( 2013 ) and varying between 60 and 670 µg/m in study reported by Sairanen ( 2014 ). However, the ambient concentrations measured in Nigeria were significantly higher (approximately ten times or more) than ambient concentrations in Finland even though sampling distance were significantly higher (5000 m) in the study conducted in Nigeria compared to the ambient sampling distances (few tens of meters) in the study conducted in Finland.…”
Section: Previous Studiesmentioning
confidence: 82%
See 2 more Smart Citations
“…The result indicates that elevated values of PM 10 were recorded in week 4, 9, 10, 11 and12 at Okigwe. This location in Imo States is known for stone mining and quarry activities within and around the area, which could contribute significantly to the concentration of particulate matter in this area [50]. Also, it could be observed that elevated level of PM 10 was recorded in Egbema.…”
Section: Resultsmentioning
confidence: 85%